2007
DOI: 10.1108/09513540710729908
|View full text |Cite
|
Sign up to set email alerts
|

An assessment system for teacher education program quality improvement

Abstract: Purpose -The purpose of this study is to describe how one US Midwestern university implements quality principles, based on the value added premise in a teacher preparation program that yields accountability, teacher education standards attainment and ultimately improvement of teacher candidates and overall programs. Design/methodology/approach -Data pertinent to students were gathered in a systematic way as they declared a certification area. This data was used to identify students who needed tutorial support … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…These data also illustrate a potential process for providing TPPs feedback on the achievement of students taught by new graduates. These types of data provide one key element of continuous improvement models, the ability to obtain repeated measurements of a relevant meaningful outcome of interest (Reusser, Butler, Symonds, Vetter, & Wall, 2007). This is not to argue that it is the only outcome that should be of interest to teacher educators.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These data also illustrate a potential process for providing TPPs feedback on the achievement of students taught by new graduates. These types of data provide one key element of continuous improvement models, the ability to obtain repeated measurements of a relevant meaningful outcome of interest (Reusser, Butler, Symonds, Vetter, & Wall, 2007). This is not to argue that it is the only outcome that should be of interest to teacher educators.…”
Section: Discussionmentioning
confidence: 99%
“…The difficulty of this task has highlighted a key challenge underlying this work. As with all value-added data, the results do not answer why a particular result occurred or what might be done to improve on it; rather, all it does is provide feedback on performance, focus program improvement efforts, and provide a benchmark that helps sustain a focus on continuous program improvement (Hart & Bogan, 1992; Reusser et al, 2007). It is interesting to note that at least two programs that engaged in the sort of self-study occasioned by the data identified plausible hypotheses regarding actions that they could and did take to improve their results.…”
Section: Discussionmentioning
confidence: 99%
“…The principal is required to deploy strategies to advance school development and improvement, and maintain the quality change. Principal is also required to help teachers who develop their knowledge, skills (Reusser et al, 2007) and understanding of ICT which have had an influence on teaching and learning in the classroom. In addition, the school-level review process should be set up properly to improve the performance of their students.…”
Section: Discussionmentioning
confidence: 99%
“…Although business and industry widely embrace CI as a way to learn from their behavior and create a competitive advantage (Stata, 1989), educational systems have been relatively slow to use the data they collect on a regular basis to engage in CI. Given that one critical element of CI is collecting repeated measurements of important outcomes (Reusser, Butler, Symonds, Vetter, & Wall, 2007), difficulties inherent in data collection and sophisticated statistical analysis have made CI difficult to implement in education.Although resource challenges historically have served as a barrier to outcomes-based assessments and CI approaches in education, systematic approaches to the evaluation of teacher performance in terms of student outcomes are increasingly evident in schools (Papay, 2010). The availability of databases that integrate student demographic data, disability data, achievement histories, classroom achievement, 579267I SCXXX10.…”
mentioning
confidence: 99%
“…Although business and industry widely embrace CI as a way to learn from their behavior and create a competitive advantage (Stata, 1989), educational systems have been relatively slow to use the data they collect on a regular basis to engage in CI. Given that one critical element of CI is collecting repeated measurements of important outcomes (Reusser, Butler, Symonds, Vetter, & Wall, 2007), difficulties inherent in data collection and sophisticated statistical analysis have made CI difficult to implement in education.…”
mentioning
confidence: 99%